Extended Abstract: File Transfer in Vehicular Ad-Hoc Networks - Ullah, Kifayat; Santos, Luz Marina; Michelin, João; Moreira, Edson dos Santos (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2013)
A large amount of file transfer systems in use today are designed to operate in wired networks. In the context of vehicular ad-hoc networks, these systems may behave improperly, due to the inherent characteristics of wireless networks and mobility of vehicles. This work proposes and implements a model for transferring files using basic client-server architecture, with focus on its operation in vehicular networks. We performed two different sets of experiments. The first experiment was performed to evaluate the performance of the system with different number of clients and servers while the purpose of second experiment was to validate the application behavior in an outdoor environment. The results show that the system is able to perform file transfers. It is concluded that the number of clients has a great impact on performance of the system.